Assessing Community Readiness and Benefits of a Nursing Program: Implications for Healthcare and Education - Mary Anne Frances D. Reyes; Aaron A. Funa; Robert Jamisola; Ma Joahna D. Perdigon; Jerica D. Latonero (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
In response to recent policy shifts allowing the establishment of new nursing programs in the Philippines, this study assesses the perceived readiness of Sorsogon, a geographically underserved province, to implement a bachelor of science in nursing program. It also explores the anticipated benefits that such a program may offer to students and the local community. A cross-sectional survey of 375 stakeholders, selected through purposive sampling, was conducted using a validated instrument developed through expert consultation. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic analysis. The findings reveal widespread support for the proposed program, emphasizing its potential to enhance clinical competence, promote holistic health, and expand access to healthcare services in the region. However, respondents also cited institutional limitations, including inadequate infrastructure and a shortage of qualified faculty. While limited by its reliance on self-reported data and geographically concentrated sampling, the study offers timely, place-based insights that can inform educational planning and equitable health workforce development in rural Philippine settings. The findings highlight the need for faculty and infrastructure investments, offering a basis for policymakers and institutions to implement nursing programs that address regional healthcare gaps. Keywords: community health, educational access, healthcare needs, nursing education, perceived benefits, professional growth Abstrak Menilai Kesiapan Komunitas dan Manfaat Program Pendidikan Keperawatan: Implikasi bagi Pelayanan Kesehatan dan Pendidikan. Sejalan dengan perubahan kebijakan terbaru yang memungkinkan pendirian program pendidikan keperawatan baru di Filipina, studi ini mengobservasi persepsi tentang kesiapan Provinsi Sorsogon sebagai wilayah yang kurang diperhatikan secara geografis untuk menyelenggarakan program sarjana keperawatan. Studi ini juga mengeksplorasi manfaat yang diharapkan dari program tersebut bagi mahasiswa dan komunitas lokal. Survei cross-sectional menggunakan instrumen tervalidasi yang dikembangkan melalui konsultasi pakar, kemudian disebarkan kepada 375 pemangku kepentingan yang dipilih melalui purposive sampling. Data kuantitatif dianalisis menggunakan statistik deskriptif, sedangkan respons kualitatif ditelaah melalui analisis tematik. Hasil menunjukkan adanya dukungan luas terhadap program yang diusulkan, dengan penekanan pada potensinya untuk meningkatkan kompetensi klinis, mempromosikan kesehatan holistik, dan memperluas akses terhadap layanan kesehatan di wilayah tersebut. Namun, responden juga menyoroti keterbatasan institusional, termasuk infrastruktur yang tidak memadai dan kurangnya tenaga pengajar berkualifikasi. Meskipun penelitian ini bergantung pada data yang dilaporkan sendiri dan pengambilan sampel yang terkonsentrasi secara geografis, studi ini menawarkan hasil penelitian berbasis lokal untuk mendukung perencanaan pendidikan dan pengembangan tenaga kesehatan yang berkeadilan di wilayah pedesaan Filipina. Temuan ini menegaskan perlunya investasi pada tenaga pengajar dan infrastruktur sebagai langkah awal bagi pembuat kebijakan dan institusi untuk menerapkan program keperawatan yang mampu menjawab kesenjangan layanan kesehatan regional. Kata Kunci: akses pendidikan, kebutuhan layanan kesehatan, kesehatan masyarakat, manfaat yang dirasakan, pendidikan keperawatan, pengembangan profesional